2021
DOI: 10.1029/2021gl092816
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Regulations Are Working—Why Is Surface Ozone Over Industrialized Areas Still High? Applying Lessons From Northeast US Air Quality Evolution

Abstract: The large fuel consumption associated with rapid development of the Chinese economy has resulted in dramatic deterioration in air quality. To mitigate air pollution, the Chinese government has implemented a series of measures that curb emissions from industry, vehicle, and power generation (China State Council [CSC], 2013. These controls have resulted in significant reductions in many of the major atmospheric pollutants such as NO x (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 51 publications
7
33
0
Order By: Relevance
“…Sicard, et al [ 38 ] reported that the lockdown during COVID-19 caused a substantial decrease in NO x (~ 56%) and an increase in O 3 (~ 36%) in Wuhan. Chen, et al [ 42 ] compared ozone pollution in China with ozone pollution in the USA in the 1990s and concluded that stricter NOx controls can improve O 3 pollutions over industrialized areas. In the abatement scenario of COVID-19, the Anhui region has not reached a NOx sensitive area.…”
Section: Resultsmentioning
confidence: 99%
“…Sicard, et al [ 38 ] reported that the lockdown during COVID-19 caused a substantial decrease in NO x (~ 56%) and an increase in O 3 (~ 36%) in Wuhan. Chen, et al [ 42 ] compared ozone pollution in China with ozone pollution in the USA in the 1990s and concluded that stricter NOx controls can improve O 3 pollutions over industrialized areas. In the abatement scenario of COVID-19, the Anhui region has not reached a NOx sensitive area.…”
Section: Resultsmentioning
confidence: 99%
“…The model configurations in this work are similar with Chen et al (2021), who have demonstrated the capability of this model to simulate surface O 3 concentrations in E. China. We refer the reader to Chen et al (2021) for the details of model configurations. The modeled NO 2 to be compared with satellite measurements (y trop ) are smoothed with OMI averaging kernels with the following approach (Huang et al 2014, Qu et al 2020):…”
Section: Geos-chem Model Simulationsmentioning
confidence: 65%
“…Regional emissions are replaced by Multiresolution Emission Inventory for China in China, and MIX in other regions of Asia (Li et al 2017). The model configurations in this work are similar with Chen et al (2021), who have demonstrated the capability of this model to simulate surface O 3 concentrations in E. China. We refer the reader to Chen et al (2021) for the details of model configurations.…”
Section: Geos-chem Model Simulationsmentioning
confidence: 82%
“…As shown in Figure 5, the NO 2 concentration clearly demonstrates a continuous decreasing trend over the YRD region during 2014-2020. In term of VOCs, we employed the column density of HCHO via satellite retrievals to represent the interannual variations of VOCs (Li R. et al, 2021). The column density of HCHO shows an inverted "U" shape, which increases from 7.2 × 10 15 molec cm 2 (2014) to 8.0 × 10 15 molec•cm 2 (2017) and then drops to 7.4 × 10 15 molec cm 2 (2020).…”
Section: Driving Factors Of Interannual Changes In O 3 From 2014 To 2020mentioning
confidence: 99%
“…However, the upward trend has significant differences in different regions and different periods. Chen et al (2021) revealed that annual O 3 concentration was in continuous increase across the YRD region during 2014-2019 but rose in volatility in the Pearl River Delta (PRD) region over the same period. In addition, the increment of O 3 in the YRD region is more obvious with a rate of 3.2 ppbv yr −1 from 50.7 to 66.3 ppbv, which is approximately four times that in the PRD region.…”
Section: Introductionmentioning
confidence: 99%